TEACHING LISTENING COMPREHENSION THROUGH MULTIMEDIA TOOLS - Orazimbetov Shingisbek,; Bekbergenova Azada, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This research examines the transformative role of multimedia and strategic instruction in developing English listening skills. By moving away from traditional audio-only methods, the study focuses on how visual aids and “metacognitive instruction” help students manage their own learning. The analysis shows that when learners use a three-stage process—planning, monitoring, and evaluating—they become more independent and less anxious. The integration of authentic videos provides real-world context, helping students improve not only their listening but also their vocabulary and critical thinking. The results suggest that a student-centered, multifaceted approach is essential for building confidence and communicative success in a global environment.